On the Meijer transformation - J. Conlan; E. L. Koh (International Journal of Mathematics and Mathematical Sciences)
Recently [8], an operational calculus for the operator Bμ=t−μDt1+μD with −1<μ<∞ was developed via the algebraic approach [4], [13], [15]. This paper gives the integral transform version. In particular, a differentiation theorem and a convolution theorem are proved.